2000
DOI: 10.1088/0264-9381/17/15/308
|View full text |Cite
|
Sign up to set email alerts
|

Geodesic motions versus hydrodynamic flows in a gravitating perfect fluid: dynamical equivalence and consequences

Abstract: Stimulated by the methods applied for the observational determination of masses in the central regions of the AGNs, we examine the conditions under which, in the interior of a gravitating perfect fluid source, the geodesic motions and the general relativistic hydrodynamic flows are dynamically equivalent to each other. Dynamical equivalence rests on the functional similarity between the corresponding (covariantly expressed) differential equations of motion and is obtained by conformal transformations. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…We are motivated by the fact that almost all mass measurements made are based on the assumption of idealized purely Newtonian-type gravitational motions, although this is only approximately true at best. To find out what ignoring the actual MHD motions means for the accuracy of an obtained mass-energy estimate, we have employed a rather simple theoretical argument which extends the work of [11,12] to magnetised environments. We have shown, in particular, that the MHD flow of the actual physical fluid can be represented as a purely gravitational motion of a virtual medium under a different, generalised gravitational potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We are motivated by the fact that almost all mass measurements made are based on the assumption of idealized purely Newtonian-type gravitational motions, although this is only approximately true at best. To find out what ignoring the actual MHD motions means for the accuracy of an obtained mass-energy estimate, we have employed a rather simple theoretical argument which extends the work of [11,12] to magnetised environments. We have shown, in particular, that the MHD flow of the actual physical fluid can be represented as a purely gravitational motion of a virtual medium under a different, generalised gravitational potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a B-field the above reduces to the expression relating the density of a physical, hydrodynamically moving, Newtonian fluid to that of its virtual counterpart with a purely Newtonian motion [11,12]. In particular, the second term on the right-hand side of the above is due to the fluid pressure, while the last two primarily convey the magnetic field contribution.…”
Section: Relation Between Physical and Virtual Densitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…We end this brief tutorial by mentioning that one of the reviewers of this manuscript kindly pointed out that Kleidis and Spyrou [14] have previously suggested that dynamical equivalence between geodesic motions and hydrodynamic flows could also introduce virtue mass terms and the modification of the gravitational potential. Their idea was based on conformal transformations, whereas the CILOMAS theory is based on the scale-running of the propagator coupling constant resulting from the classical RG transformations.…”
Section: Summary and Brief Conclusionmentioning
confidence: 99%